Sargassum crasifolium Extract Could Prevent the Decrese in the Thyroxine Hormone and the Body Weight Loss of Javanese Randu Goats during Transportation - Claude Mona Airin; Amelia Hana; Sarmin; Pudji Astuti; Amir Husni; Rusyda Nurshitaningrum (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
Thyroxine hormone (T4) was one of the hormones related to metabolism rate. Animal transportation could be stressor interfering metabolism. Sargassum crasifoium was one of brown algae species that contained some important nutrients and also flavonoids. The study aimed at finding out the effect of the Sargassum on the decrase in thyroxine hormone and body weight loss. It used 9 Javanese Randu goats that were classified into 3 treatment groups. Group I served as control, Group II was treated with 450 mg/kg BW of Sargassum estract and Group III was treated with vitamin B1. All of the goats were transported for 12 hours using pickup truck at the speed of 60 km/hour. Blood samples were drawn before the transportation, during loading, 6 hours after the transportation and at the end of the transportation, while the body weight of the goats was weighed before and after the transportation. The results of the study showed that the T4 hormone decreased in the Group I and increased in the Group III during the transportation, while it was stable in the Group II. The biggest percentage of the body weight loss took place to the Group III (0.13%), while the smallest percentage took place to the Group II (0.063%). Statistical analysis showed that the Sargassum extract did not have any significant effect (p>0.05) on both the thyroxine hormone and the body weight loss during the transportation. Based on the results of the study it could be concluded that the Sargassum extract could stabilize the thyroxine hormone during the transportation so that it could prevent the body weight loss